Construindo a qualidade da educação jurídica : limites e possibilidades da aprendizagem baseada em problemas - Ustárroz, Elisa (2016)
The aim of this dissertation is to understand to what extent problem-based learning (PBL) can contribute to enhance legal education. Beyond this general objective, the research pursued the following specific objectives: (i) to reflect on the concept of quality in higher education in the current context of the Brazilian educational system; (ii) to investigate the crisis in the Brazilian legal education in the present scenario; (iii) to conduct a literature review on the application of PBL in law schools by identifying the limits and possibilities of the methodology in order to foster the academic formation of the desired students. The research is based on the conception of social constructivism and qualitative-exploratory approaches (CRISWELL, 2010). Regarding the procedure, it is a literature review of the scientific production about the quality of higher education, legal education and application of PBL in law schools. The theoretical foundations of these investigations were based on the contributions of Dewey (1979), Barrows (1999), Morosini (2001; 2008; 2009; 2011) and Rodrigues (1993; 1995; 2000; 2002; 2005; 2007; 2010). The results showed that PBL can improve the quality in legal education, as it promotes learning by skills, one of such being the critical and reflective thinking. In addition, it favors both collaboration and autonomy, allowing for the construction of a new concept of teaching process based on partnership, mutual respect and shared responsibility. On the other hand, it was found that its contributions may not be as effective if cultural influences and institutional constraints suffered by students and teachers alike are neglected. The success is conditioned to a permanent reflection by all those involved in the teaching and learning process.